Degree apprenticeships: Reflecting on university–employer partnership practice to improve workforce development in the United Kingdom. Issue 6 (December 2019) - Welbourn, Jane; Devins, David; Reynolds, Martin
This article offers an early assessment of the extent and scope of participation by higher education institutions (HEIs) in Degree Apprenticeship (DA) provision for meeting the broader workforce development objectives of the UK Government. While the take-up of DAs by HEIs and businesses has been undeniably lower than the publicly declared Government targets, the issues seem to be related to matters of institutional 'stickiness' in HEIs and implementation practicalities for businesses. The article reflects on the institutional dynamics involved in HEIs' collective shifting of their practice in response to Government intervention to associate funding with HE–business collaboration. The authors' observations are drawn from the experience of one HEI; they adopt an auto-ethnographic perspective to reflect on the role of the DA model as one way of stimulating how HEIs can work with businesses to co-design workforce development initiatives and offer ideas for future development.